2023
DOI: 10.1126/sciadv.adc8825
|View full text |Cite
|
Sign up to set email alerts
|

Escape from NK cell tumor surveillance by NGFR-induced lipid remodeling in melanoma

Abstract: Metastatic disease is a major cause of death for patients with melanoma. Melanoma cells can become metastatic not only due to cell-intrinsic plasticity but also due to cancer-induced protumorigenic remodeling of the immune microenvironment. Here, we report that innate immune surveillance by natural killer (NK) cells is bypassed by human melanoma cells expressing the stem cell marker NGFR. Using in vitro and in vivo cytotoxic assays, we show that NGFR protects melanoma cells from NK cell–mediated killing and, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Sanchez-Del-Campo et al demonstrated that the MITF low melanoma cell population can be reduced by NK cell-mediated killing, whereas MITF high cells can escape NK cell surveillance [60]. On the contrary, the most recently published study revealed that overexpression of NGFR in melanoma cells resulted in a reduction of NK cell infiltration into xenografts and NK cell-mediated melanoma cell killing [61]. The authors suggest that NGFR is a promising therapeutic target in melanoma and genetically engineered chimeric antigen receptor (CAR)-NGFR NK cells might be used against melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez-Del-Campo et al demonstrated that the MITF low melanoma cell population can be reduced by NK cell-mediated killing, whereas MITF high cells can escape NK cell surveillance [60]. On the contrary, the most recently published study revealed that overexpression of NGFR in melanoma cells resulted in a reduction of NK cell infiltration into xenografts and NK cell-mediated melanoma cell killing [61]. The authors suggest that NGFR is a promising therapeutic target in melanoma and genetically engineered chimeric antigen receptor (CAR)-NGFR NK cells might be used against melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Other markers beyond MITF and AXL can give insight to melanoma phenotypes produced by EMT. For example, increased nerve growth factor receptor (NGFR) can mark a post-EMT state ( 25 ) associated with T cell resistance ( 14 ) and NK cell resistance, enhancing metastatic potential ( 110 ). EMT is a process at the cellular level, but also the tumoral level.…”
Section: Immune Escape and Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%
“…Importantly, CD271 has been linked to immune escape in multiple reports. CD271 can be induced by IFNγ, which is produced in high volumes by NK cells, thus contributing to immune escape by driving the downregulation of melanoma antigens [250,251]. If future CAR-NK studies can be designed to secrete a synthetic peptide that can inhibit CD271, this may be able to restore endogenous effector cell recruitment for concerted tumor cell elimination alongside CAR-NK cells.…”
Section: Potential Targets For Car-nk Cell Therapies In Melanomamentioning
confidence: 99%